Tax Competition for FDI in Central-European Countries - Milan Sedmihradsky; Stanislav Klazar (Center for Economic Studies and ifo Institute (CESifo), 2002)
Most governments of the Central and East European countries adopted in 1990s tax measures for a support of foreign direct investments. Such measures usually include 10-year tax holidays and exemption from import duties. They are mostly accompanied by grants for building an infrastructure and creation of new jobs. As our data indicate and the statistical test has proved, the incentives are effective in attracting new FDI to the countries. However there are some indicators that a tax competition between the CEE countries exists.
Keywords: 330